2019
DOI: 10.24176/re.v9i2.3383
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Whatsapp Application for Teaching Integrated English (A Case Study at University of Technology Yogyakarta)

Abstract: This study aimed to illustrate some learning activities in Integrated English class byutilizing WhatsApp application and how the students respond to its implementation. The study was conducted in Accounting Department at University of Technology Yogyakarta. The subject of this study was 66 students in Accounting Class A of 2018/2019 Academic Year. The instruments to gather the data were observation, questionnaires and unstructrured interview. The result of this study showed that WhatsApp Application could be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The second most frequently used digital platform in this study is WhatsApp Group which is a more cost-effective option. Several studies have established this fact (Dewi, 2019;Iswati, 2021;Kholis, 2020;Rinekso & Muslim, 2020;Suadi, 2021). Based on the study of Kholis (2020), because it was easy, light, and inexpensive, the WhatsApp app is ideal for studying English from a distance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most frequently used digital platform in this study is WhatsApp Group which is a more cost-effective option. Several studies have established this fact (Dewi, 2019;Iswati, 2021;Kholis, 2020;Rinekso & Muslim, 2020;Suadi, 2021). Based on the study of Kholis (2020), because it was easy, light, and inexpensive, the WhatsApp app is ideal for studying English from a distance.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed that the virtual ELT class in the form of Zoom and WhatsApp was regarded positively by the students since they were also rated effective and efficient in terms of time, place, and cost. In addition to this, students could use WhatsApp as one of the helpful tools to learn integrated English (Dewi, 2019). To enhance more fun EFL teaching and learning activities, Google Meet for teachers' positive perspective and attitude (Souheyla, 2022), Google Classroom, and WhatsApp can be used in tandem (Sunardi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the teachers lead the mathematics learning community with ICT by utilising recording videos or direct WhatsApp videos to guide the parents (not the students) who would like to assist their children in learning mathematics. It was convinced that the application of ICT, especially the inclusion features of videos, tremendously improve students' learning (Dewi, 2019;Gon & Rawekar, 2019). Nevertheless, the studies focused on the learning of learning subjects other than mathematics, such as science-based and languagebased content (Dewi, 2019;Grover et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was convinced that the application of ICT, especially the inclusion features of videos, tremendously improve students' learning (Dewi, 2019;Gon & Rawekar, 2019). Nevertheless, the studies focused on the learning of learning subjects other than mathematics, such as science-based and languagebased content (Dewi, 2019;Grover et al, 2020). Therefore, this study has added some value to applying WhatsApp in teaching mathematics.…”
Section: Discussionmentioning
confidence: 99%
“…This feature makes the application ultimate for language teaching and learning (Ahmed, 2019;Mbukusa, 2018;Nuraeni & Nurmalia, 2020). For example, some studies (Dewi, 2019;Hamad, 2017;Kheryadi, 2018;Urien et al, 2019) establish that integrating WhatsApp into the teaching and learning process helps students to build confidence and interest. Such advantages manifest when students use WhatsApp to improve their vocabulary, verbal interaction outside the classroom, and writing skills (Ahmed, 2019).…”
Section: Whatsapp In Educationmentioning
confidence: 99%